2015
DOI: 10.1016/j.bbamem.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Cationic amphipathic peptides KT2 and RT2 are taken up into bacterial cells and kill planktonic and biofilm bacteria

Abstract: We investigated the mechanisms of two tryptophan-rich antibacterial peptides (KT2 and RT2) obtained in a previous optimization screen for increased killing of both Gram-negative and Gram-positive bacteria pathogens. At their minimal inhibitory concentrations (MICs), these peptides completely killed cells of multidrug-resistant, enterohemorrhagic pathogen Escherichia coli O157:H7 within 1-5 min. In addition, both peptides exhibited anti-biofilm activity at sub-MIC levels. Indeed, these peptides prevented biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 31 publications
1
66
0
Order By: Relevance
“…It was proposed that these peptides could traverse inside the cell and eventually bind the DNA for its antimicrobial action (Anunthawan et al . ). Bacteriocin isolated from Citrobacter freundii showed antimicrobial activity against a wide range of bacteria including E. coli in both planktonic as well as in biofilm form (Shanks et al .…”
Section: Therapeuticsmentioning
confidence: 97%
“…It was proposed that these peptides could traverse inside the cell and eventually bind the DNA for its antimicrobial action (Anunthawan et al . ). Bacteriocin isolated from Citrobacter freundii showed antimicrobial activity against a wide range of bacteria including E. coli in both planktonic as well as in biofilm form (Shanks et al .…”
Section: Therapeuticsmentioning
confidence: 97%
“…For example, Anunthawan et al . demonstrated that the two tryptophan-rich cationic antimicrobial peptides KT2 and RT2 showed anti-biofilm activity at sub-MIC levels against the multidrug-resistant, enterohemorrhagic E. coli O157:H7 strain and were able to prevent biofilm formation and eradicate mature biofilms at a concentration of 1 μM [13]. Both peptides interacted with and bound to negatively-charged LPS molecules to enable self-promoted uptake (without forming pores or aggregates) across the outer membrane and subsequently interacted with cytoplasmic membrane phospholipids [13].…”
Section: Antimicrobial Peptides With Potential To Fight Biofilm-relatmentioning
confidence: 99%
“…On one hand, the cell wall of gram-positive bacteria represents a porous 40-to 80-nm-thick mesh that many AMPs seem to pass with relative ease (Malanovic and Lohner 2016). On the other, gram-negative bacteria present an outer membrane that some AMPs can quickly cross by a charge-exchange mechanism where the cationic peptides compete with Ca 2+ and Mg 2+ bound to lipopolysaccharide, possibly promoted by binding to outer membrane proteins (self-promoted uptake hypothesis; e.g., Anunthawan et al 2015). These peptides then have access to the cell wall in gram-negative bacteria as well as the cell membrane and intracellular targets.…”
Section: Crossing the Outer Membrane Of Gram-negative Bacteriamentioning
confidence: 99%